2023
DOI: 10.1126/scisignal.abn9909
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of signaling through the common FcRγ chain determine cytokine profiles in dendritic cells

Abstract: The common Fc receptor γ (FcRγ) chain is a signaling subunit common to several immune receptors, but cellular responses induced by FcRγ-coupled receptors are diverse. We investigated the mechanisms by which FcRγ generates divergent signals when coupled to Dectin-2 and Mincle, structurally similar C-type lectin receptors that induce the release of different cytokines from dendritic cells. Chronological tracing of transcriptomic and epigenetic changes upon stimulation revealed that Dectin-2 induced early and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…These receptors include pathogen recognition receptors (PRR) like C-type lectin receptors (CLRs), a superfamily of proteins that interact with several types of sugars on the surface of pathogens and have a crucial role in the capture and presentation of the antigen, and Toll-like receptors (from TLR1 to TLR10), both primarily involved in the recognition of pathogen-associated molecular patterns (PAMPs) ( 28 ). DCs also express Scavenger receptors like CD36 ( 29 , 30 ) involved in the uptake of a variety of ligands, including lipids, apoptotic cells, and microbial components as well as several other receptors such as chemokines receptors, complement receptors and Fc receptors, all regulating antigen presentation functions ( 31 ). In the sections that follow, we provide a more detailed description of such receptors and their respective ligands.…”
Section: Immune Cell Targeting Why?mentioning
confidence: 99%
See 2 more Smart Citations
“…These receptors include pathogen recognition receptors (PRR) like C-type lectin receptors (CLRs), a superfamily of proteins that interact with several types of sugars on the surface of pathogens and have a crucial role in the capture and presentation of the antigen, and Toll-like receptors (from TLR1 to TLR10), both primarily involved in the recognition of pathogen-associated molecular patterns (PAMPs) ( 28 ). DCs also express Scavenger receptors like CD36 ( 29 , 30 ) involved in the uptake of a variety of ligands, including lipids, apoptotic cells, and microbial components as well as several other receptors such as chemokines receptors, complement receptors and Fc receptors, all regulating antigen presentation functions ( 31 ). In the sections that follow, we provide a more detailed description of such receptors and their respective ligands.…”
Section: Immune Cell Targeting Why?mentioning
confidence: 99%
“…Macrophages express several receptors that that could be targeted for vaccine delivery such as TLRs ( 28 ), mannose receptors ( 86 ), scavenger receptors ( 29 ) and Fc receptors ( 31 ). Targeting this cell population is particularly interesting for respiratory infections, since alveolar macrophages are the first cells to present pathogens to pulmonary draining lymph nodes ( 87 ).…”
Section: Target Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported previously that the quantity and duration of FcRγ signaling may induce distinct signaling through the common FcRγ subunit. 42,48,49 Considering these findings, the differences in ligand structures may affect the kinetics and strength of Mincle-FcRγ signaling, potentially generating different gene expression profiles. Further research is necessary to understand their effects on host biological processes, including the immune system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our study of a single-cell dataset using the signaling pathway of the IL1RN gene showed that IL1RN expression in glioma-associated macrophages changes from low to high. TNF, NF-κB, osteoclast differentiation, and SYK pathways may explain these findings [ 69 ]. We speculate that after SIRPB1 deletion, inadequate early SYK phosphorylation could impact downstream pathways.…”
Section: Discussionmentioning
confidence: 99%